CAUSALITY AMONG BOOK VALUE, EARNING PER SHARE AND STOCK PRICE: A STUDY OF INDIAN COMPANIES - Agrawal, Om Prakash; Bansal, Prateek Kumar (International Journal of Psychosocial Rehabilitation, 2020)
This research is an attempt to examine the relationship among Book Value (BV), Earning Per Share (EPS) and Stock Price of the selected Indian Companies listed in stock exchange. it is very important for investor to know the factors influencing stock price. To check the relationship among BV, EPS and stock price various statistical tools i.e. regression analysis, correlation and unit root have been applied with the help of Eviews. Sample size is of 114 companies listed in Indian stock exchange on the basis of their incorporation before the year of 2000 and data of 19 years have been collected. Findings of the study indicates positive relationship among dependent and independent variable.